How can patients with mobile hips and stiff lumbar spines be identified prior to total hip arthroplasty?: a prospective, diagnostic cohort study - Innmann, Moritz Maximilian; Merle, Christian; Phan, Philippe; Beaulé, Paul E.; Grammatopoulos, George (The journal of arthroplasty, 2020)
Background: Patients with reduced lumbar spine mobility are at higher risk of dislocation following total hip arthroplasty (THA). Therefore our study aimed to (1) define the optimal protocol for identifying patients with mobile hips and stiff lumbar spines and (2) determine clinical and standing radiographic parameters predicting these patients. Methods: A cohort of 113 patients with end-stage hip osteoarthritis awaiting THA was prospectively studied. Clinical data, patient-reported outcome measures, and spinopelvic radiographs were assessed with the patient in the standing, “relaxed-seated,” and “deep-flexed seated” position. A “hip user index” was calculated quantifying the percentage of sagittal hip movement compared to overall movement between the standing and deep-flexed seated position. Results: Radiographs in the relaxed-seated position had an accuracy of 56% (95% confidence interval 46-65) to detect patients with stiff lumbar spines, compared to a detected rate of 100% in the deep-flexed seated position. A standing pelvic tilt of ≥19° was the only predictor for being a hip user with a sensitivity of 90% and specificity of 71% (area under the curve 0.83). Patients with a standing pelvic tilt ≥19° and an unbalanced spine with a flatback deformity had a 30× fold relative risk (95% confidence interval 4-226, P < .001) of being a hip user. Conclusion: Patients awaiting THA and having combined high hip and reduced lumbar spine mobility can be screened for with lateral standing radiographs of the spinopelvic complex. Hip user verification should be done utilizing radiographs in the deep-flexed seated position due to a higher accuracy compared to relaxed-seated radiographs. Level of Evidence: Level II, diagnostic study.
Gesehen am 22.06.2020